A multifaceted coating on titanium dictates osteoimmunomodulation and osteo/angio-genesis towards ameliorative osseointegration. (April 2018) - Bai, Long; Du, Zhibin; Du, Jingjing; Yao, Wei; Zhang, Jiaming; Weng, Zeming; Liu, Si; Zhao, Ya; Liu, Yanlian; Zhang, Xiangyu; Huang, Xiaobo; Yao, Xiaohong; et al.
Abstract: A multifaceted coating for hard tissue implants, with favorable osteogenesis, angiogenesis, and osteoimmunomodulation abilities, would be of great value since it could improve osseointegration and alleviate prosthesis loosening. However, to date there are few coatings that fully satisfy these criteria. Herein we describe a microporous TiO2 coating decorated with hydroxyapatite (HA) nanoparticles that is generated by micro-arc oxidation of pure titanium (Ti) and followed annealing. By altering the annealing temperature, it is possible to simultaneously tune the coating's physical (morphology and wettability) and chemical (composites and crystallinity) properties. A coating produced with micro-arc oxidization (MAO) with an annealing temperature of 650 °C (MAO-650) exhibits numerous favorable physicochemical properties, such as hybrid micro-nano morphology, superhydrophilicity, and highly crystalline HA nanoparticles. In vitro experiments reveal that the MAO-650 coating not only supports proliferation and differentiation of both osteoblasts and endothelial cells, but also inhibits the inflammatory response of macrophages and enables a favorable osteoimmunomodulation to facilitate osteo/angio-genesis. In vivo evaluation mirrors these results, and shows that the MAO-650 coating results in ameliorative osseointegration when compared with the pristine MAO coating. These data highlight the profound effect of surface physicochemical properties on the regulation of osteo/angio-genesis and osteoimmunomodulation in the enhancement of osseointegration. Graphical abstract: